2018
DOI: 10.1016/j.heliyon.2018.e00973
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal, anti-oxidant activity and cytotoxicity of South African medicinal plants against mycotoxigenic fungi

Abstract: Fungal strains belonging to genus Fusarium and Aspergillus are known to infect crops, resulting in threatened food security and less agricultural crop yields. The aim of the current work was to investigate the anti-mycotoxigenic activity, cytotoxic effect and antioxidant potential of selected South African medicinal plants extracts. The aqueous and organic extracts of the leaves from selected medicinal plants were investigated for their antifungal activity against various fungal strains that are known to infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In the present study, Ziziphus mucronata did not show any cytotoxicity effects with LC 50 values of 2582.656 µg/ml against RAW 264.7 cells, however, it was toxic against C2C12 cells with LC 50 value of 150.210 µg/ml. Previous studies have reported cytotoxicity of Ziziphus mucronata with LC 50 value ranged from 0.10 µg/ml to 0.22 µg/ml against Bovine dermis and Vero cells (Mongalo et al, 2018). In other studies, no cytotoxicity was reported for Z. mucronata in RAW 264.7 cells with LC 50 value as low as >50 µg/ml.…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, Ziziphus mucronata did not show any cytotoxicity effects with LC 50 values of 2582.656 µg/ml against RAW 264.7 cells, however, it was toxic against C2C12 cells with LC 50 value of 150.210 µg/ml. Previous studies have reported cytotoxicity of Ziziphus mucronata with LC 50 value ranged from 0.10 µg/ml to 0.22 µg/ml against Bovine dermis and Vero cells (Mongalo et al, 2018). In other studies, no cytotoxicity was reported for Z. mucronata in RAW 264.7 cells with LC 50 value as low as >50 µg/ml.…”
Section: Discussionmentioning
confidence: 90%
“…, Mahonia aquifolium Nutt. , Glycyrrhiza glabra L. and so on, were reported to exert antifungal activity [813]. In our screening study, we found that Maianthemum japonicum ( A.…”
Section: Introductionmentioning
confidence: 85%
“…The phytochemicals that produce medicinal plants derived from their secondary metabolism represent a safe and effective alternative to control various phytopathogens that affect various crops of agricultural products of economic and nutritional Table 4. Secondary metabolites of medicinal plants with biological activity against phytopathogens [86][87][88][89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%